Respuesta :

Answer:

2√3

Step-by-step explanation:

root 27

= √27

= 3√3

12 upon root 3

= 12 / √3

= ( 12 / √3 ) x ( √3 / √3 )

= ( 12 x √3 ) / ( √3 x √3 )

= 12√3 / 3

= 4√3

6 upon √3

= 6 / √3

=  ( 6 / √3 ) x ( √3 / √3 )

= ( 6 x √3 ) / ( √3 x √3 )

= 6√3 / 3

= 2√3

root 3 = √3

root 3 + root 27 - 12 upon root 3 + 6 upon root 3

= √3 + 3√3 - 4√3 + 2√3

= 4√3 - 4√3 + 2√3

= 2√3

Answer:

2√3

Step-by-step explanation:

Our equation :

  • [tex]\sqrt{3} + \sqrt{27} - \frac{12}{\sqrt{3} } + \frac{6}{\sqrt{3} }[/tex]

Simplifying

  • [tex]\sqrt{3} + \sqrt{9 *3} - \frac{12\sqrt{3} }{\sqrt{3}*\sqrt{3} } + \frac{6\sqrt{3} }{\sqrt{3}*\sqrt{3} }[/tex]
  • [tex]\sqrt{3}+3\sqrt{3} - \frac{12\sqrt{3} }{3}+\frac{6\sqrt{3} }{3}[/tex]
  • [tex]4\sqrt{3}-4\sqrt{3}+2\sqrt{3}[/tex]
  • 2√3